1974
DOI: 10.1021/ja00816a009
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical kinetics of the retro-ene reactions of molecules with the general structure (allyl)XYH in the gas phase. 6. Concerted unimolecular decomposition of hepta-1,6-diene

Abstract: The kinetics of the thermal decomposition of hepta-1,6-diene (HD) have been studied in the gas phase over the temperature range 628-744 °K. Propylene and butadiene in essentially equimolar concentrations are the major reaction products, with 4-methylcyclohexene, cyclopentene, and ethylene as minor detectable side products at large conversions. First-order rate constants for the disappearance of HD, obtained by an internal standard technique, fit the Arrhenius relationship, log k, sec-1 = 11.31 ± 0.44 -(47.00 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…For the thermal intramolecular retroene reaction (H) Smith and Yates [60] reported an activation energy of 170 kJ mol −1 for the retro-ene reaction of 4-hydroxy-4-methyl-1-pentene producing propylene and acetone. Egger et al [61] found similar values for other types of compounds that are able to undergo thermal retro-ene rearrangements. It was found that this activation energy resulted in retro-ene kinetics that underestimated yields of compound 9 and produced significant yields of compound 8.…”
Section: Activation Energiesmentioning
confidence: 70%
See 1 more Smart Citation
“…For the thermal intramolecular retroene reaction (H) Smith and Yates [60] reported an activation energy of 170 kJ mol −1 for the retro-ene reaction of 4-hydroxy-4-methyl-1-pentene producing propylene and acetone. Egger et al [61] found similar values for other types of compounds that are able to undergo thermal retro-ene rearrangements. It was found that this activation energy resulted in retro-ene kinetics that underestimated yields of compound 9 and produced significant yields of compound 8.…”
Section: Activation Energiesmentioning
confidence: 70%
“…Smith and Yates [60] reported a pre-exponential factor of 2.0 × 10 11 s −1 for the retro-ene reaction of 4-hydroxy-4-methyl-1-pentene producing propylene and acetone. Egger et al [61] found similar values for other types of compounds that are able to undergo retro-ene rearrangements. This value is adopted in the current kinetic models.…”
Section: Pre-exponential Factorsmentioning
confidence: 72%
“…Unimolecular rate constants based on the disappearance of hex-1-ene and the formation of ethylene were obtained over the temperature range of 915-1153 K using all three reactor exit apertures. They were calculated from the mass-spectral peak intensities and calibration data in the usual way [12,15]. The rate constants for the retro-ene pathway were then obtained by difference.…”
Section: Resultsmentioning
confidence: 99%
“…4, 5 and 8). Thermolysis of similar 1,6-heptadienes yields fragmentation products exclusively [48]. The only condition for those cyclizations that has to be fulfilled, is the absence of an internal carbon-carbon double bond in conjugation to one of the others in 1-or 6-position (e.g.…”
Section: Reactivity Of the Acyclic Main Productsmentioning
confidence: 99%